William Henry Dunning: The Quiet Man - Findlay, Michael (Architectural History Aotearoa, 2004)
Tasmanian-born architect William Henry Dunning (1872-1933) commenced his New Zealand practice in Timaru in 1907. Initially trained in Hobart, under the notable church designer Alexander North, Dunning’s experience as a colonial architect was further extended in Cape Town. His association with fellow Tasmanians Alfred and Sidney Luttrell drew him to Dunedin where he supervised the construction of the New Zealand Express Company Building. Dunning was an ambitious architect. His competition entries included designs for the New Zealand Parliament Buildings (1911) and the Auckland War Memorial Museum (1922). Despite the quality of his work, and efforts towards self-promotion, Dunning’s most significant contribution to the city’s architecture, the National Bank (1911) has been frequently attributed to another designer. The remainder of his work is also little known. This paper seeks to explore the ways in which architects asserted authorship during the period and will attempt to map the shifting responsibilities between architects and builders that allowed Dunning’s contribution to the National Bank project to become obscured.